Spinal cord compression due to extramedullary hematopoiesis in a patient with E-beta-thalassemia managed without radiation or surgery. Issue 4 (4th July 2018) - La, Van T.; Diatte, Michael; Gaston, Johnathan; Dick, Dallas; Sweiss, Raed; Pakbaz, Zahra
ABSTRACT: Extramedullary hematopoiesis (EMH) in individuals with thalassemia is often the result of undertreated severe anemia. Radiation or surgery is often the chosen approach to handle spinal cord compression due to these paraspinal EMH elements. Our patient is a 28-year-old male with E-beta-thalassemia who presented with both upper thoracic and lower extremity symptoms of spinal cord compression and was successfully managed with the combination of transfusion and hydroxyurea. Given the variation in symptoms as a result of the sporadic location as well as the extent of these EMH elements along the spinal canal, the hematological communities will continue to benefit from case reports that offer treatment therapy.